PENGARUH STRATEGI PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN LITERASI MEMBACA PEMAHAMAN SISWA KELAS V SD NEGERI UJUNG TANAH 2 KOTA MAKASSAR - Madinah Tulmunawwara; Sukri Syamsuri; Syahruddin Syahruddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
Reading comprehension literacy is a crucial skill that elementary students must develop to support their learning across various subjects. However, differences in students’ abilities, interests, and preferred learning styles often present challenges to mastering this skill. This study examines the effect of implementing differentiated instruction strategies on the reading comprehension literacy of fifth-grade students at SD Negeri Ujung Tanah 2 in Makassar. The research utilized a pre-experimental design with a one-group pretest-posttest approach, involving 30 students from class VA. Data collection was conducted through reading comprehension tests administered before and after the intervention. The results showed a significant increase in the average score, from 33.67 on the pretest to 79.00 on the posttest. A paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating that the differentiated instruction strategy significantly improved students’ reading comprehension literacy. Nonetheless, 37% of the students did not reach the minimum competency criteria, highlighting the need for further refinement of the approach. In conclusion, while differentiated instruction effectively enhances reading comprehension literacy, it requires ongoing development to better accommodate the varied learning needs of all students.